Frottage : frictions of intimacy across the black diaspora - Macharia, Keguro (Sexual cultures., 2019)
"In Frottage, Keguro Macharia weaves together histories and theories of blackness and sexuality to generate a fundamentally new understanding of both the black diaspora and queer studies. Macharia maintains that to reach this understanding, we must re-think not only the historical and theoretical utility of identity categories such as gay, lesbian, and bisexual; but also more foundational categories such as normative and non-normative, human and non-human. Simultaneously, Frottage questions the heteronormative tropes through which the black diaspora has been imagined. Between Frantz Fanon, René Maran, Jomo Kenyatta, and Claude McKay, Macharia moves through genres--psychoanalysis, fiction, anthropology, poetry--as well as regional geohistories across Africa and Afro-diaspora to map the centrality of sex, gender, desire, and eroticism to black freedom struggles. In lyrical, meditative prose, Macharia invigorates frottage as both metaphor and method with which to rethink dispora by reading--and reading against--discomfort, vulnerability, and pleasure."--Page [4] of book cover.